Avkokskomprimering till CBG-lager som avkokshantering på LBG-tankstationer - Levin, Olle (2019)
The number of fuel stations for liquefied biogas or liquefied natural gas (LBG or LNG, both composed of liquid methane) in Sweden will increase in the coming few years, from 6 stations to over 30 in total. While there still are very few LNG heavy-duty vehicles (HDV's) on Swedish roads, technical problems may arise at fuel stations due to low consumption. As boil-off gas (BOG) accumulates and causes overpressure, there will be a need to vent or torch BOG to reduce this pressure, unless the BOG is handled some other way. There are several BOG management techniques. At an LBG fuel station with LCBG liquefied to compressed biogas) equipment, a compressor can be added to compress BOG to the CBG storage. If there are vehicles demanding CBG fuel, they may consume BOG and compensate for low LBG demand. There are over 50,000 CBG vehicles in Sweden, and their demand for CBG could help manage BOG problems at underutilised LBG fuel stations.